Mayer-Rokitansky-Kuster-Hauser (MRKH) Syndrome A Case ReportRT (Journal of Paediatric Surgeons of Bangladesh, 2014)
We report a case of Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome in a 25 year old married lady. Though it is a congenital abnormality, she presented as primary infertility after 2 year of her marriage and was referred to us from a Gynaecologist. She had absent vagina, rudimentary uterus with no cervix. Her ovaries were severely hypoplastic. The anus was placed anteriorly and opened into the vulva. In spite of absence of her vagina, the lady somehow maintained her married life by doing intercourse through the anteriorly placed rectum. The vagina was made from the lower end of existing rectum which opened into the vulva. The proximal end of the rectum and left colon were pulled through the pelvis and opened into the perineum. It improved her quality of life.DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19468